Impact Of Psoriasis on The Quality of Life - Yogesh M Shah; Kaushur Didarally Khodabocus; Yugantara R Kadam; Alka D Gore; Kirti C Rasote (Medsci Publications, 2015)
Background: The Quality of Life of a patient of psoriasis is similar to or worse than a patient of chronic diseases like ischemic heart dis- ease, hypertension, diabetes and cancer, however no assessment of the same was available in Mauritius. Aim was to do a quantitative study of impact of psoriasis on the Quality of Life of the psoriatic. Methods: A cross-sectional study of consecutive 55 patients of pso- riasis was carried out at the Skin Outpatient department of a regional hospital in Mauritius. An assessment of impact of psoriasis on the Quality of Life of each patient of psoriasis was carried out using the Psoriasis Disability Index Questionnaire of A Y Finlay. Results: Out of total 55 patients of psoriasis 30 (54.6%) had PDI score ≥ 20 and 25 (45.4%) patients < 20; 14/19 (73.70%) women had PDI score >20. (p value=0.024). The impact of psoriasis on the 'daily activ- ities' of the psoriatic scored highest with (62.3%), followed by 'lei- sure' (39.2%), 'at work' (33.3%), 'treatment' (29.3%) and 'personal relationships' (8.1%). Conclusions: The majority of the psoriatic had a severe negative im- pact on their Quality of Life which was most obvious in their 'daily activities' and in women.